Uji Kimia Sirup Jeruk Gerga (Citrus Nobilis Sp.) dengan Variasi Kadar Gula dan Sari Buah Jeruk Gerga - Desta Ria Erika; Inka Rizki Padya (Jurnal BETAHPA, 2023)
Gerga orange is one of the potential crops in Pagaralam City. However, not many people know the contents of gerga oranges. As the planting area increases, there is also an increase in the number of gerga orange products. This results in abundant fruit stocks. One of the weaknesses of the Gerga orange fruit is that it is perishable and its shelf life is relatively low. The high water content in Gerga orange fruit causes the orange to become soft and easily rot on the surface and inside the skin. Fruit with high water content can experience mechanical damage, decreased fruit mass, respiration rate, and high transpiration rate. Therefore, during harvest and post-harvest a handling process is required. This research aims to determine the chemical characteristics of gerga orange syrup with variations in sugar content and orange juice. The ratio of orange juice has a significant effect on the water content, pH, and total sugar of gerga orange syrup. Variations in sugar content have a significant effect on the water content, pH and total sugar of Gerga orange syrup. This shows that variations in sugar content and Gerga orange juice affect the chemical characteristics of Gerga orange syrup. The interaction between fruit juice and variations in sugar content did not have a significant effect on the water content, pH and total sugar of gerga orange syrupGerga orange is one of the potential crops in Pagaralam City. However, not many people know the contents of gerga oranges. As the planting area increases, there is also an increase in the number of gerga orange products. This results in abundant fruit stocks. One of the weaknesses of the Gerga orange fruit is that it is perishable and its shelf life is relatively low. The high water content in Gerga orange fruit causes the orange to become soft and easily rot on the surface and inside the skin. Fruit with high water content can experience mechanical damage, decreased fruit mass, respiration rate, and high transpiration rate. Therefore, during harvest and post-harvest a handling process is required. This research aims to determine the chemical characteristics of gerga orange syrup with variations in sugar content and orange juice. The ratio of orange juice has a significant effect on the water content, pH, and total sugar of gerga orange syrup. Variations in sugar content have a significant effect on the water content, pH and total sugar of Gerga orange syrup. This shows that variations in sugar content and Gerga orange juice affect the chemical characteristics of Gerga orange syrup. The interaction between fruit juice and variations in sugar content did not have a significant effect on the water content, pH, and total sugar of gerga orange syrup.